Program of Health Promotion and Values Education through film and video in La Rioja (1995-2012) - Purificación Echeverría Cubillas; Mª Luisa Rodríguez Moroy (Universidad de La Rioja, 2014)
In this paper we describe the Program for Promotion of Health and Education in Values through Film and Video, aimed at the students of 4th of Secondary Education (ESO) and of 1st of Professional Qualification Programs (PCPI) in the Autonomous Community of La Rioja during the period of 1995-2012. Its main assumption is that movies can be used as an important educational resource to promote health culture in schools. The main outputs of the program were that the participation of schools remained stable over the years, with minor variations between the 70/80%, and that the program was well received by teachers and students, who made a positive assessment thereof. Besides, it must be highlighted the high percentage of students (between 80/90%) indicating the usefulness of the activities carried out to generate reflection after watching the movies.